If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9D + 4 = 6D + -8 Reorder the terms: 4 + 9D = 6D + -8 Reorder the terms: 4 + 9D = -8 + 6D Solving 4 + 9D = -8 + 6D Solving for variable 'D'. Move all terms containing D to the left, all other terms to the right. Add '-6D' to each side of the equation. 4 + 9D + -6D = -8 + 6D + -6D Combine like terms: 9D + -6D = 3D 4 + 3D = -8 + 6D + -6D Combine like terms: 6D + -6D = 0 4 + 3D = -8 + 0 4 + 3D = -8 Add '-4' to each side of the equation. 4 + -4 + 3D = -8 + -4 Combine like terms: 4 + -4 = 0 0 + 3D = -8 + -4 3D = -8 + -4 Combine like terms: -8 + -4 = -12 3D = -12 Divide each side by '3'. D = -4 Simplifying D = -4
| 4.6+x=9.3 | | 5/12=20/g | | 6h-6=20 | | 2.2k=7.92 | | ln(20x+14)=3 | | 1x+7=49 | | 8ax=25a-15x | | (6h)-6=20 | | 9D+4=6Dplus-8 | | 3b-6=38 | | (-6h)-6=20 | | x^2+243=0 | | 4(m-1)+2(3-4m)=-5(m+2)+2 | | 90+4=60+-8 | | -2-15y+6=3y+5-y | | 240+80v=688-2v | | e^3+3=3 | | 15a-12-a=(5a+6) | | 6(x+1)+6=3x+3(3+x) | | .66w=9 | | (g*4)-3= | | 2n(n-7)+3=9 | | 70+6log(x)=40 | | 3b-6=15 | | 4(w-8)-(-2w-3)=5w | | 29t-17.5=12.9 | | 8Y-4=8Y+5 | | 2d+12=24 | | 0.12(y-3)+0.16y=0.20y-0.01(20) | | 4x-9*4= | | 8(x-2)+2=6(2x-7) | | (2z+5)(1+z)=0 |